(untitled) (Journal of Science and Technology, 2016)
Imports are very crucial for the survival of a small open economy such as Ghana. In this paper, we estimate an import demand function for Ghana for the period 1970 to 2002, as well as consider the time series properties of the data. The time series behaviour of the data indicates a long term relationship between real exchange rates, GDP, and merchandise import. Our empirical estimates suggest that real income (GDP) is the main factor influencing imports in Ghana. The results also indicate that economic growth (real GDP) and depreciation in the local currency could stimulate increased demand for merchandise imports. Further analysis revealed that shocks to imports, real GDP and real exchange rate are important in explaining various innovations in the error variance of each of these variables at different time horizons and at different magnitudes. Particularly, the evidence shows that at short time periods about 65%, 95% and 80% of shocks to real exchange rates, merchandise imports and GDP respectively, are attributed to own shocks.